Singular matrices that are products of two idempotents or products of two nilpotents - Călugăreanu Grigore (Special Matrices, 2021)
Over commutative domains we characterize the singular 2 × 2 matrices which are products of two idempotents or products of two nilpotents. The relevant casees are the matrices with zero second row and the singular matrices with only nonzero entries.